An overview of systematic reviews of acupuncture for diabetic gastroparesis - Li, Ting; Yu, Mingchen; Han, Lulu; Feng, Bo; Sun, Fenglei (Frontiers in Medicine, 2023)
Background To date, several systematic reviews and/or meta-analyses (SRs/MAs) on the topic of acupuncture as a treatment for diabetic gastroparesis (DGP) have been published. However, whether acupuncture is an effective and safe treatment for DGP remains controversial. In this study, we aimed to determine whether the methodology and results of previously published SRs/MAs of acupuncture as a treatment for DGP were of sufficient quality to be considered reliable. Methods We extensively searched seven databases, including PubMed, EMBASE, Cochrane Library, Web of Science, China National Knowledge, Wan Fang, and Chongqing VIP, for SRs/MAs published before or on September 16, 2022. The SRs/MAs that met the inclusion criteria were evaluated for the quality of the methodology and results using the Assessing the Methodological Quality of Systematic Reviews Two (AMSTAR-2) and Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) tools. A re-meta-analysis of primary outcome indicators was also performed. Results Ten SRs/MAs that met the inclusion criteria were obtained. Using the AMSTAR-2, which is a methodological quality assessment tool, two MAs were rated as low quality, and eight SRs/MAs were rated as extremely low quality. Assessment with the GRADE tool revealed that, among 20 results, 4 were of moderate quality, 10 were of low quality, and 6 were of very low quality. Re-meta-analysis of primary outcome indicators revealed that, in terms of total efficiency, all types of acupuncture interventions, such as acupuncture, electroacupuncture, and acupoint injection, performed better than the controls, such as gastroprokinetic agents and sham acupuncture. Moreover, in the treatment of DGP, acupuncture exhibited fewer side effects compared to the controls. Conclusion Acupuncture appears to improve the symptoms of patients with DGP, and the side effects of acupuncture as a treatment for DGP are inferior to those of the controls. However, owing to the low quality of the methodology and results of the SRs/MAs, these findings cannot be considered reliable and need to be validated by additional studies with rigorous standards of experimental design and protocols and larger sample sizes.